(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
The aging process is accompanied by a multitude of physiological changes, and one of the most crucial organs affected is the heart. This scientific article explores the age-related alterations in cardiac physiology, encompassing structural, functional, and molecular aspects. Through an analysis of current research findings, this article aims to shed light on the complex interplay of factors that contribute to the aging heart’s decline in function. Understanding these changes is essential for developing strategies to promote healthy aging and mitigate cardiovascular diseases in the elderly population.